Plant diversity of ala-archa national park in kyrgyzstan with emphasis on its economical potential - (:unkn) unknown (Springer International Publishing, 2018)
The national parks are the most important tools in biodiversity conservation. The generally include remote and rugged areas possessing a low possibility for human use. They are of lower economic value. Currently the Republic of Kyrgyzstan possesses a total of eight national parks. These cover approximately 1.4% of national territory. One of these national parks is the Ala-Archa National Park. During the period covering the months from May to October, every weekend hundreds of visitors pay a visit to this oldest national park of the country established in 1976. The 25 km long park has a total area of 194 km2. This area encompasses the upper watershed of the Ala-Archa River. The park shows a microclimate of almost every ecosystem existing in the Republic of Kyrgyzstan, including the forests of mixed conifers, deciduous and dwarf juniper forests, scrubland, grassland steppe, sagebrush semidesert, river valleys, glaciers, and high alpine environments. The total number of vascular plants growing in the national park is 756 taxa. These belong to 73 families and 324 genera. Six hundred twenty-three taxa are from the dicotyledonous group, whereas 121 taxa are from the monocotyledonous group. This chapter presents an analysis of the economical potential of plant diversity of this national park. © Springer Nature Switzerland AG 2018.
Keywords: Ala-archa national park; Economic potential; Plant diversity